Alternative distribution and its role in the promotion of films produced by the Irzykowski Film Studio between 1981–1984 - Sowiński, Emil (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The Irzykowski Film Studio was founded in 1981 as an institution that allowed young filmmakers to start their careers directly after graduating from the Film School. The studio could produce medium-length and short feature films and documentaries as well as animation. Nevertheless, all these types of films, according to the statute confirmed by the minister, were not to be officially cinema distributed, since they were supposed to be treated as a film exercise, a kind of practice run. Finally, it turned out that the Irzykowski Film Studio productions were regarded as fully fledged films that could compete with films produced by Film Units (i.e., the professional organizational entities of the Polish film production system at the time) or short film studios. What is not without significance, most films (not to say: all) were politically controversial. Therefore, the leaders of the Studio decided to show films to the audience, but they could not do it officially by applying for referral to cinema distribution. In connection with this, they were shown at small film festivals, inner (unofficial) screenings, and illegally distributed on VHS tapes. By extension, the range of distribution was narrow, but, curiously enough, the films were attracting a lot of interest from film critics, audiences and... state authorities. The aim of this paper is to analyze the alternative distribution process that occurred at the Irzykowski Film Studio. What films were shown at festivals, at internal screenings, and which were illegally copied onto VHS tapes? Had all the films shown been censored? How did state censorship react to test screenings with the audience? How did the critics and audience perceive these films? Did the presence of films at festivals influence their cinema distribution? And finally: how did the promotion and festival distribution of these films affect the perception of the Irzykowski Film Studio among the state authorities?